2018
DOI: 10.2147/ott.s164670
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin induces apoptosis in human pancreatic cancer cells via the mitochondrial-mediated intrinsic pathway and suppresses tumor growth in vivo

Abstract: BackgroundCordycepin, the main active ingredient of a traditional Chinese herbal remedy – extracted from Cordyceps sinensis – has been demonstrated as a very effective anti-inflammatory and antitumor drug. The present study investigated its antitumor effect on pancreatic cancer, a highly aggressive cancer with extremely poor prognosis due to malignancy, and clarified its underlying mechanism both in vitro and in vivo.MethodsThe antitumor viability of cordycepin on human pancreatic cancer MIAPaCa-2 and Capan-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…[33][34][35] Previous studies have confirmed that caspases and Bcl-2 family proteins, such as Bax and Bcl-2, serve important roles in the mitochondrial apoptotic pathway. [36][37][38] Mortenson et al 39 demonstrated that bortezomib triggered cell apoptosis in small cell lung cancer via decreasing Bcl-2 levels. The results of the present study revealed that nitroxoline markedly decreased the level of Bcl-2, and increased the levels of Bax, cleaved PARP and cleaved caspase-3 in a concentration-dependent manner in H929 and RPMI8226 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Previous studies have confirmed that caspases and Bcl-2 family proteins, such as Bax and Bcl-2, serve important roles in the mitochondrial apoptotic pathway. [36][37][38] Mortenson et al 39 demonstrated that bortezomib triggered cell apoptosis in small cell lung cancer via decreasing Bcl-2 levels. The results of the present study revealed that nitroxoline markedly decreased the level of Bcl-2, and increased the levels of Bax, cleaved PARP and cleaved caspase-3 in a concentration-dependent manner in H929 and RPMI8226 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with cordycepin also induces apoptosis through the mitochondria-mediated intrinsic apoptotic pathways indicated by translocation of Bax from the cytosol to the mitochondria, release of cytochrome c from the mitochondria to the cytosol, and activation of caspase-9. Caspase-9 is activated by apaf-1 (apoptosome) and activates caspase-3 and -7 [57,58]. In addition, treatment with cordycepin induces death receptor-mediated extrinsic apoptotic pathways, as indicated by the activation of caspase-8, which stimulates two parallel cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Colony formation assay indicated that Se-enriched Cordyceps militaris plays an important role in the reduction of cell proliferation in NCI-H292 and A549 cells. Many anticancer drugs could target cell apoptosis to induce the death of cancer cells 25. Flow cytometric assay and Hoechst staining analysis demonstrated the promotive efficacy of Se-enriched Cordyceps militaris in NSCLC cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-apoptotic member BAX and the anti-apoptotic member BCL-2 belong to the BCL family 6. BCL-2 could prevent the release of cytochrome c, while the activation of BAX leads to the release of cytochrome C into the cytosol, resulting in activation of caspases 9 and 3, effector caspases, in the mitochondrial pathway of cell apoptosis 25,26. In this study, we found that the ratio of BCL-2/BAX at both mRNA and protein levels was reduced as the concentration of Se-enriched Cordyceps militaris increased in both NCI-H292 and A549 cells, indicating the pro-apoptotic role of Se-enriched Cordyceps militaris in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%